2013
DOI: 10.1159/000353487
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Angiomyxoma with Diffusion-Weighted Magnetic Resonance Imaging and Dynamic Contrast Enhancement: A Case Report and Review of the Literature

Abstract: Introduction: Aggressive angiomyxoma (AA) is a rare benign soft tissue tumour usually affecting the pelvis and perineum of young women. Magnetic resonance imaging (MRI) is crucial in the management of AA patients for its diagnostic contribution and for the preoperative assessment of the actual tumour extension. Given the current development of less aggressive therapeutics associated with a higher risk of recurrence, close follow-up with MRI is fundamental after treatment. In this context, diffusion-weighted (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Brunelle et al described a case of an aggressive pelvic angiomyxoma in a 51-year-old female patient in whom a multi-modal examination was performed. The tumor was hyperintense on DWI images at b0 and b1000 with a high ADC of 2 × 10-3 mm 2 /sec, similar to what is found in myxoid tumors [10]. The dynamic enhancement examination of this tumor after gadolinium showed gradual enhancement with no plateau or washout, suggesting that it was fibrous in nature.…”
Section: Discussionsupporting
confidence: 68%
“…Brunelle et al described a case of an aggressive pelvic angiomyxoma in a 51-year-old female patient in whom a multi-modal examination was performed. The tumor was hyperintense on DWI images at b0 and b1000 with a high ADC of 2 × 10-3 mm 2 /sec, similar to what is found in myxoid tumors [10]. The dynamic enhancement examination of this tumor after gadolinium showed gradual enhancement with no plateau or washout, suggesting that it was fibrous in nature.…”
Section: Discussionsupporting
confidence: 68%
“…Owing to the ability to provide valuable qualitative and quantitative features of the tumor, DWI has been a hot topic in oncology. There are some articles reported the DWI of AA showed a high value of tumor ADC measurement more than 2 × 10 -3 mm 2 /sec [7,8] as in our second case. The S Brunelle, et al observed DWI showed heterogeneous high signal intensity both on b0 and b1000 images [8].…”
Section: Figure 4bsupporting
confidence: 56%
“…There are some articles reported the DWI of AA showed a high value of tumor ADC measurement more than 2 × 10 -3 mm 2 /sec [7,8] as in our second case. The S Brunelle, et al observed DWI showed heterogeneous high signal intensity both on b0 and b1000 images [8]. However in our second case, we only observed high signal intensity on b0 images.…”
Section: Figure 4bsupporting
confidence: 56%
See 1 more Smart Citation
“…The surgery of wide local excision is the mainly option in the measurements [7,8]. The rate of local recurrence of AA is different from reports but shows a decrease pattern in recent years.…”
Section: Figure 4bmentioning
confidence: 94%